2021
DOI: 10.1590/1677-5449.200243
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic internal carotid artery dissection and kinking in a patient with fibromuscular dysplasia

Abstract: Isolated dissection of the internal carotid artery (ICA) is rare in young patients and is a cause for strong suspicion of fibromuscular dysplasia (FMD), especially when associated with artery elongation and tortuosity. The natural history of cerebrovascular FMD is unknown and management of symptomatic patients can be challenging. We report the case of a 44-year-old female patient with a history of transient ischemic attack in the absence of cardiovascular risk factors, associated with an isolated left ICA diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The management and outcome of these cases differed according to the case [ Table 1 ]. [ 4 , 5 , 8 , 16 , 17 , 19 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The management and outcome of these cases differed according to the case [ Table 1 ]. [ 4 , 5 , 8 , 16 , 17 , 19 ]…”
Section: Resultsmentioning
confidence: 99%
“…Bilman et al 2021 [4] 44 We reviewed the literature for the reported cases of localized FMD involving the ICA. Only six cases consisted of localized carotid artery FMD; almost all of these cases involved the left-sided ICA.…”
Section: Antiplatelet Agents Goodmentioning
confidence: 99%